Belarusian youth in the digital environment: modern Internet use practices - Nedelevskaya, Ilona G. (Journal of the Belarusian State University. Sociology, 2025)
The article reveals the key features of digital practices of Belarusian youth, as determined by a questionnaire survey of students of three higher education institutions in Grodna. The current trends concerning the purposes, nature and time of their use of the Internet are revealed. Popular platforms, preferred types of content, as well as the level of young people’s involvement in various forms of Internet activity are considered. Special attention is paid to the role of social networks in the spheres of leisure, education, work and communication of young Belarusians. The changes in students’ media consumption practices over the last 15 years are noted.
Keywords: youth; digital practices; Internet activity; social networks; messengers; media consumption; Internet communication; Belarus